Contemporary Security Challenges and Its Effects on Nigeria’s Foreign Relations, 2015-2022 - Ahmed Audu Yusufu (Covenant University Journal of Politics and International Affairs, 2022)
The nefarious activities of Boko Haram terrorists, armed bandits, herders-farmers clashes and Indigenous People of Biafra (IPOB) among others have devastating effects on Nigeria’s national security. Efforts by the federal government at curtailing their activities notwithstanding, these criminal elements have continued to operate with impunity; killing, maiming and raping of innocent citizens across the country. Boko Haram terrorists mostly operate in the North-East Region while armed herders violently attack sedentary crop farmers in the North-Central; the North-West and South-East Regions have been riddled by the activities of armed bandits and IPOB members respectively. Consequently, the security situation in the country is deteriorating with debilitating consequences on her foreign relations. Relying on exegesis of relevant secondary sources such as books, journals, newspapers and web-based materials among others; the paper posits that the nefarious activities of Boko Haram terrorists, armed bandits, IPOB members and violent herders among other criminal elements threatens Nigeria’s national security, which by extension affects her foreign relations. The paper concludes that the country’s security situation may further deteriorate as long as the government keeps politicizing insecurity in the country. The paper therefore recommends, among other things, that the government should stop politicizing insecurity and stand up to its primary responsibility of securing the lives and property of its citizens while at the same time delivering dividends of democracy in an atmosphere of good governance characterized by freedom, equity and justice.